Diagnostic Imaging of Acute Appendicitis in Reproductiveage - Wanwarang Suthikeeree (The Royal Thai College of Obstetricians and Gynaecologists, 2012)
Acute pelvic pain is a common presenting symptom in reproductive-age women. This condition may be associated with gynecologic disease such as pelvic inflammatory disease, ruptured ovarian cyst or nongynecologic conditions including gastrointestinal or urinary tract diseases. Acute appendicitis, the most common cause of nongynecologic pain may mimic the more common gynecologic conditions, due to nonspecific signs and symptoms. Therefore, diagnostic imaging is necessary. Transabdominal and/or transvaginal ultrasound (US) is the preferred imaging modality for initial assessment when an obstetrical or gynecologic etiology is suspected. If the result is inconclusive or normal, computerized tomography (CT) should be performed. Currently CT is the imaging modality of choice for diagnosis of acute appendicitis in adult. The diagnosis of acute appendicitis on both US and CT examination are based on evidence of an inflamed appendix, showing fluid-filled distension, enlarged appendix (greater than 6 mm), appendiceal wall thickening with enhancement and/or appendicolith. Periappendiceal inflammatory change are also seen. In perforated appendicitis, more specific findings are extraluminal air, extraluminal appendicolith, pericecal phlegmon or abscess and defect in enhancing appendiceal wall.